(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this article, I argue that the category of gender should be an essential consideration for a decolonised curriculum, and that gender theory should be included in its analytical toolbox for two reasons: firstly, because transformation of the curriculum has to foreground women’s liberation by validating their experiences of, and contributions to, the past, and secondly, because gender has functioned as a key axis of power between men and women in the past. This study undertakes a critical analysis of the knowledge about women and gender forwarded by the current CAPS curriculum statement. Part of my objective is to reflect on what kinds of historical knowledge about women are considered “legitimate” by the curriculum, and to evaluate the ways in which this knowledge sustains or challenges an otherwise androcentric or masculinist history. In the main, however, I aim to show the ways in which the existing framework governing the South African history curriculum is unable to accommodate the kinds of knowledge and conceptual thinking required to give depth and meaning to women’s experiences, and to examine how race and gender interact to produce and reproduce hierarchies and highly complex social relations. Feminist historians of empire and post-colonialism have long argued that race and class are gendered categories, and that gendered meanings therefore fundamentally shaped the imperial and colonial project. Gendering history in the South African curriculum would therefore entail revisiting many topics currently included in the curriculum and explicitly foregrounding the ways in which gender has functioned as a significant axis of power. This will not be a comfortable experience, especially given its implication in colonial violence, apartheid and the liberation struggle. Nonetheless, a number of FET topics deeply transformed by inclusion of this scholarship would open up new paradigms for negotiating the relationship between the past and the present.